1969
DOI: 10.1042/bj1110479
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of ubiquinone in relation to thyroxine status

Abstract: 1. Under conditions of thyrotoxicosis induced by feeding rats with iodinated casein, ubiquinone concentration was found to increase in the liver by increased synthesis and by partly decreased catabolism leading to its accumulation. The increased ubiquinone was found primarily in the mitochondrial and supernatant fractions. 2. Supplementing the diet with thyroxine, at less than toxic doses, also increased the synthesis and the concentration of ubiquinone in the liver. 3. In the condition of hypothyroidism obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Some information is available regarding the effects of thyroid hormone on vitamin E and Coenzyme Q, present at relatively high concentrations in the inner mitochondrial membrane, where they reduce free radical-initiated lipid peroxidation [162,163]. Early studies showed that hyperthyroidism increases the content of ubiquinone [97,164], but does not modify vitamin E content in liver mitochondria [12]. More recently, the increase in ubiquinone content and lack of changes in vitamin E content, besides being confirmed in the liver, has also been shown in cardiac and skeletal muscle from hyperthyroid rats [96].…”
Section: Mitochondrial Oxidative Damage and The Antioxidant Defence Smentioning
confidence: 98%
“…Some information is available regarding the effects of thyroid hormone on vitamin E and Coenzyme Q, present at relatively high concentrations in the inner mitochondrial membrane, where they reduce free radical-initiated lipid peroxidation [162,163]. Early studies showed that hyperthyroidism increases the content of ubiquinone [97,164], but does not modify vitamin E content in liver mitochondria [12]. More recently, the increase in ubiquinone content and lack of changes in vitamin E content, besides being confirmed in the liver, has also been shown in cardiac and skeletal muscle from hyperthyroid rats [96].…”
Section: Mitochondrial Oxidative Damage and The Antioxidant Defence Smentioning
confidence: 98%
“…In rat liver, the occurrence of CoQ10 is about 175 nmol/g fresh tissue [49]. However, coenzyme Q levels are substantially depleted in the liver of a starved animal and could be too low to be detected in such a case [50]. Therefore, the effect of the endogenous CoQ 10 on the finding of this study was likely to be negligible, as the liver microsomes used were prepared from the fasted rats.…”
Section: Discussionmentioning
confidence: 94%
“…Our results for the serum substrate revealed that the primary disturbed statistically significant pathways (p < 0.05), in response to hypothyroidism, were aminoacyl-tRNA biosynthesis, phenylalanine, tyrosine and tryptophan biosynthesis, phenylalanine metabolism and ubiquinone and other terpenoid-quinone biosyntheses (Table S3). The relationship between the ubiquinone metabolism and thyroxine status has been reported since the late 1960s, with higher levels of thyroxine leading to higher ubiquinone concentrations and accumulations in the liver due to an increased biosynthesis and to a partly decreased catabolism [56]. Specifically, the pathways of importance containing at least two compounds involve phenylalanine, tyrosine and tryptophan biosynthesis, aminoacyl-tRNA biosynthesis and the phenylalanine metabolism.…”
Section: Metabolitepathway Analysismentioning
confidence: 99%